Pengaruh Luas Lahan, Kelembagaan Dan Tingkat Pendidikan Terhadap Kesejahteraan Kelompok Petani Ternak Sapi Potong Dengan Modal Sebagai Variabel Moderasi di Desa Paya Bakung, Kabupaten Deli Serdang - Aisyah Citra Dewi; Nur Ahmadi Bi Rahmani (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2022)
The process of integrating production components such as land, livestock, labor, and capital to produce livestock products is known as livestock business. In addition, management and management in the livestock industry are closely related to the socio-economic characteristics of breeders, which will have an impact on the results that can be achieved by the breeders themselves. Utilizing a quantitative methodology, this research. Using the Moderated Regression Analysis (MRA) test, the Coefficient of Determination, T test, and F test are used as data analysis tools. SPSS version 22 analytical program was used to perform the test. According to research findings, well-being is significantly influenced by educational attainment and institutional size. Cattle breeders in Paya Bakung village. However, the welfare of the farmer groups in Paya Bakung village is only slightly affected by land area. The welfare of livestock herds in Paya Bakung village is simultaneously significantly influenced by land area, institutional quality, and level of education. However, capital weakens the influence of institutions, education levels, and land area on the walfare of livestock farming groups.